Cerebral Mask of Takotsubo Syndrome - M. A. Tyapkina; A. A. Ordyakova; E. Yu. Ponomareva; E. V. Yakovleva (Архивъ внутренней медицины, 2025)
Takotsubo Syndrome (TS) is an acutely developing and typically reversible myocardial dysfunction, predominantly affecting the left ventricle, which clinically and electrocardiographically resembles acute coronary syndrome. Among the etiological factors of this pathology, severe emotional stress and physical conditions, including severe brain diseases, are noted. The most common symptoms in the acute phase include chest pain and dyspnea, while palpitations and syncope occur less frequently. Severe cases of TS may be complicated by cardiogenic shock, pulmonary edema, acute cerebrovascular accident, cardiac arrest. The presented clinical case demonstrates an atypical course of TS, in which the severity of the patient’s condition was determined by central nervous system involvemen.tA 68-year-old man was admitted in critical condition to the intensive care unit: after experiencing severe emotional stress, he was found unconscious at home. Upon examination, the patient was in a state of sopor with right-sided gaze paresis, right-sided mouth corner drooping, and severe neurological deficit, as assessed by NIHSS.Computed tomography of the brain revealed a poorly defined ischemic lesion in the vascular territory of the left middle cerebral artery. Electrocardiography showed biphasic and negative T waves in AVL, V3-V6. Echocardiography revealed a reduction in left ventricular ejection fraction to 32 % and the regional walls motion abnormality including circular hypokinesis. Elevated levels of myocardial necrosis markers were observed. A diagnosis of combined ischemic brain and myocardial injury was established, and treatment was initiated. The following day, significant positive dynamics were observed—the patient regained consciousness, had no neurological deficit. Magnetic resonance imaging of the brain did not reveal evidence of stroke. There are no negative and biphasic T waves on the electrocardiogram, echocardiography demonstrated normalization of left ventricular ejection fraction and the absence of hypokinetic zones. The correlation between disease onset and severe emotional stress, the discrepancy between the regional walls motion abnormality and the vascular territory of a single coronary artery with circular involvement of the left ventricle, the absence of a morphological substrate explaining the pronounced neurological deficit in the acute phase, and the quick, complete recovery of cardiac and neurological function led to the conclusion of a primary form of TS. A catecholamine surge induced acute left ventricular dysfunction, which was further complicated by cerebral hypoperfusion with progressive brain edema.So, in the acute phase TS may mimic not only the typical anginal form of myocardial infarction but also a cerebral event.